The efficient circulating immunoscore predicts prognosis of patients with advanced gastrointestinal cancer - Yamei Zhao; Yan Tang; Hanlin Qin; Kehai Feng; Changlu Hu (World Journal of Surgical Oncology, 2022)
Abstract Background Immunoscore from tumor tissues was initially established to evaluate the prognosis of solid tumor patients. However, the feasibility of circulating immune score (cIS) for the prognosis of advanced gastrointestinal cancers (AGC) has not been reported. Material and methods Peripheral venous blood was collected from 64 untreated AGC patients. We utilized flow cytometry to determine several immune cell subpopulations, including CD8+ and CD4+ T cells, NK cells, and CD4 + CD25 + CD127low Tregs. The circulating immune score 1 (cIS1) was assessed according to the proportions of CD4+, CD8+ T cells, and NK cell, whereas circulating immune score 2 (cIS2) was derived from the proportions of CD4+, CD8+ T cell, and CD4 + CD25 + CD127low Tregs. The prognostic role of cIS for progression-free survival (PFS) and overall survival (OS) was analyzed using Kaplan–Meier curves and Cox multivariate models. Receiver operating characteristic (ROC) curves were depicted to compare the prognostic values of cIS1 and cIS2. Results AGC patients with high cIS1(≥ 2) and cIS2(≥ 2) had significantly longer PFS (cIS1: median PFS, 11 vs. 6.7 months, P = 0.001; cIS2: 12 vs. 5.8 months, P < 0.0001) and OS (cIS1: median OS, 12 vs. 7.9 months, P = 0.0004; cIS2: 12.8 vs. 7.4 months, P < 0.0001) than those with low cIS1 and low cIS2. The areas under ROC curves (AUROCs) of cIS1 and cIS2 for OS were 0.526 (95% confidence interval; 95% CI 0.326–0.726) and 0.603 (95% CI 0.427–0.779, P = 0.332), whereas AUROC of cIS2 for PFS was larger than that of cIS1 0.735 (95% CI 0.609–0.837) vs 0.625 (95% CI 0.495–0.743) (P = 0.04)). Conclusion The cIS can be applied to predict the prognosis of untreated AGC patients. Compared with cIS1, cIS2 displayed superior prognostic value for PFS prediction.